Silencing of Rieske Iron-Sulfur Protein Impacts Upon the Development and Reproduction of Spodoptera exigua by Regulating ATP Synthesis - Shi, Song; Zuo, Hongliang; Gao, Lu; Yi, Xin; Zhong, Guohua (Frontiers in Physiology, 2018)
Rieske iron-sulfur protein (RISP) is a key protein subunit of mitochondrial complex III, which plays an important role in the respiratory electron transport chain. The complete cDNA of RISP was cloned from Spodoptera exigua by RT-PCR and RACE technology and named as SeRISP (GenBank accession No.: JN992290). Multiple alignments and phylogenetic tree revealed that RISPs are highly conserved among different insects, and the highly conserved region of RISPs is mainly located at the C-terminal which was the functional domain of RISP. Expression pattern analysis demonstrated that SeRISP is expressed in all developmental stages of S. exigua, the expression level is increased with larva growth, remained stable during the developmental stages from fourth instar to pupa and reached peak in adult. In addition, SeRISP was significantly suppressed by dsRNA at mRNA and protein level through dsRNA feeding from the second instar, and the suppression rates were increased with the increasing dsRNA concentration and continuous treatment time. After the silence of SeRISP in larvae, ATP synthesis and larval growth are significantly inhibited, which could cause deficiency of energy reserve in pupae and the suppression in fecundity and hatchability in adult. The silence of SeRISP in this study proved the possibility to silence the target gene in S. exigua through dsRNA feeding, and revealed the essential role of RISP in the process of ATP synthesis, as well as the growth and reproduction.